Regra-matriz de incidência tributária do imposto territorial rural - Acquaro, Marcela Conde (2010)
This paper intends to undertake a study of legal standards in our legal system take care of the rural land tax, your institution, regulation, tax collection, among other aspects. For that, at baseline, we established assumptions and concepts, for, after, we dedicate to the topic itself. We decided to make the study of the ITR through rule-array of tax incidence. Thus, we analyzed all the elements contained in the rule-array, the antecedent of its standard criteria material, temporal and spatial, while the consequent, we saw the staff and quantitative criteria. How we treat the test material, we intend to define the scope to be taken to property taxation. At the time criterion, we study the moments of occurrence of the legal fact, and, finally, on the criteria of the antecedent of the rule, we verify the criterion space and its various conflicts, what is meant by urban and rural areas, where the parameters for imposition of property tax or ITR, among other issues. Already in relation to consequent of the norm in the criteria staff, established the subject of the relationship by checking who may appear as a taxpayer's tax liability and asset. No quantitative criterion, we did extensive research to go into current discussions about the exclusions from the calculation basis permitted by law, discussions covering the delivery of the ADA - Declaratory Act Environmental wetlands by hydroelectric plants, among others. Finally, we make our conclusions as to the doctrinal or jurisprudential discussions